PENYUTRADARAAN KOMEDI SATIRE MELALUI TOKOH PROTAGONIS PADA FILM SMART? - Muhammad Bilal; Cito Yasuki Rahmad (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2018)
Is the film SMART? is a fictional film with the genre of comedy satire delivered through the protagonist. SMART film? tells the story of Shabrina, a teenager who is overused in using a smartphone and has an impact on everyday life. Through the Comedy satire genre approach on SMART films? expected to be easily accepted by the audience. SMART film? conveying messages to the audience will have a negative and positive impact on using smartphones excessively among teenagers. Through narrative and mise en scene elements, the director tells the story by dividing it into three rounds, the comedy satire scene, setting, make up, wardrobe, and player movements. Through the message conveyed by the director invites the audience to reflect on themselves in addressing smartphone use.Keywords: Directing, Comedy Satire, Protagonist Figure, Smartphone.